Foundations for the future: The potential of multimodal technologies for learning mathematics - Hegedus, S.J.; Tall, D.O. (Handbook of International Research in Mathematics Education: Third Edition, 2015)
Keywords: dept.edu

Adapting to the redesigned ap us history course - Santos, Brenda (Journal of the Gilded Age and Progressive Era, 2015)
Keywords: dept.edu

The impact of technology-enhanced curriculum on learning advanced algebra in US high school classrooms - Hegedus, Stephen J.; Dalton, Sara; Tapper, John R. (Educational Technology Research and Development, 2015)
We report on two large studies conducted in advanced algebra classrooms in the US, which evaluated the effect of replacing traditional algebra 2 curriculum with an integrated suite of dynamic interactive software, wireless networks and technology-enhanced curriculum on student learning. The first study was a cluster randomized trial and the second was a quasi-experimental replication study using a subset of the original treatment teachers. Both studies demonstrated significant impact on student learning of core algebra concepts including both procedural and conceptual problems. Various variables were modeled to understand the impact of such an intervention including demographic factors and class level. We found that being in an honors class significantly predicts learning gains but being in a non-honors SimCalc class significantly predicts learning gains versus all other groups. We also found significant effects of treatment on difference scores for problems which demanded simple procedural approaches and those that demanded complex conceptual understanding.
Keywords: Advanced algebra; Classroom connectivity; HLM; Randomized trial; SimCalc; Simulations; dept.edu

Exploring lake erie algae growth in an algebra class using geogebra - Nabbout-Cheiban, Marie (North American GeoGebra Journal, 2015)
Keywords: dept.edu; ⛔ No DOI found